Sensitivity of classification criteria from time of diagnosis in an incident systemic lupus erythematosus cohort: a population-based study from Norway - Øyvind Molberg; Karoline Lerang; Cathrine Brunborg; Helga Sanner; Antonela Botea; Anniken Orre; Nenad Damjanic; Sigrid Reppe Moe; Gro Årthun Wivestad; Heidi Kverneggen Øvreås; Thea Bjerkestrand Bøe; Garen Torhild (RMD Open)
Objectives To compare the sensitivity of 2019 European Alliance of Associations for Rheumatology/American College of Rheumatology (EULAR/ACR) classification criteria against 1997 ACR criteria for systemic lupus erythematosus (SLE), for incident SLE cases in the presumably complete population-based Nor-SLE cohort from Southeast Norway (2.9 million inhabitants).Methods All cases International Statistical Classification of Diseases and Related Health Problems, Tenth Revision (ICD-10) coded as SLE during 2000–2017 were individually reviewed. Those with a confirmed SLE diagnosis by expert clinical assessment were included in the Nor-SLE cohort. Core clinical data were recorded, and the cases were classified according to 2019 EULAR/ACR and 1997 ACR criteria. Juvenile SLE was defined as <16 years at diagnosis and adult SLE was defined as ≥16 years at diagnosis.Results We included 737 incident SLE cases (701 adults, 36 juveniles). At diagnosis, 2019 EULAR/ACR criteria were more sensitive than 1997 ACR criteria for adults (91.6% vs 77.3%; p<0.001), but not for juveniles (97.2% vs 88.9%). The 2019 EULAR/ACR counts at diagnosis differed by age group and ethnicity, being higher in young cases and those originating from Asia. From time of diagnosis to study end the fulfilment rate of 2019 EULAR/ACR criteria for the adult cohort increased from 92.5% and 86.5% to 94.6% and 91.0%, respectively, for females and males (mean disease duration of 7.5 years).Conclusion Showing 92% criteria fulfilment already at time of SLE diagnosis by 2019 EULAR/ACR criteria versus 77% by 1997 ACR criteria, the results from this population-based study suggest that the 2019 EULAR/ACR criteria will achieve its goal of capturing more early-SLE cases for clinical trials.